1996
DOI: 10.1126/science.271.5252.1123
|View full text |Cite
|
Sign up to set email alerts
|

Locus Control Region Function and Heterochromatin-Induced Position Effect Variegation

Abstract: Human CD2 locus control region (LCR) sequences are shown here to be essential for establishing an open chromatin configuration. Transgenic mice carrying an hCD2 mini-gene attached only to the 3' CD2 transcriptional enhancer exhibited variegated expression when the transgene integrated in the centromere. In contrast, mice carrying a transgene with additional 3' sequences showed no variegation even when the latter integrated in centromeric positions. This result suggests that LCRs operate by ensuring an open chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(243 citation statements)
references
References 36 publications
9
233
1
Order By: Relevance
“…It is known that an incomplete LCR loses this property when integrated into a heterochromatic region. 21,22 As two of the four transgenic lines that we have generated had the transgene in the centromeric region, and both were expressing human enzyme according to their copy number, we conclude that the fragment of murine MHC class II Ea d LCR used, with its 5 DNase hypersensitive sites, 18 can fully act as an LCR when linked to genomic sequences of a heterologous gene. The same fragment was previously used linked to the cDNA encoding Bruton tyrosine kinase (BTK).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It is known that an incomplete LCR loses this property when integrated into a heterochromatic region. 21,22 As two of the four transgenic lines that we have generated had the transgene in the centromeric region, and both were expressing human enzyme according to their copy number, we conclude that the fragment of murine MHC class II Ea d LCR used, with its 5 DNase hypersensitive sites, 18 can fully act as an LCR when linked to genomic sequences of a heterologous gene. The same fragment was previously used linked to the cDNA encoding Bruton tyrosine kinase (BTK).…”
Section: Discussionmentioning
confidence: 77%
“…Without the use of an LCR-like element integration of the gene into heterochromatin, which makes up a large part of the genome, would result in position effects and low levels of expression. 21,22 Immunofluorescent staining of spleen single cell suspensions with the rabbit polyclonal antibody R386 against human ␤-glucocerebrosidase showed that approximately 60% of the cells from transgenic spleens were positive for the human enzyme ( Figure 4d) which is the same as the percentage of B cells present in the organ. From double staining with B and T cell markers (data not shown), expressing cells are indeed B220 positive and therefore B but not T cells are responsible for the activity in the spleen.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the dominant intermolecular recombination mechanism in mammalian cells is non-homologous, the predominant head-to-tail array strongly suggests a process of homologous recombination between multiple copies (Brouillette & Chartrand, 1987;Bishop & Smith, 1989). The integration of pronuclear injected DNA was demonstrated by in situ hybridization in diverse regions of the mouse genome (Michalova et al 1988;Festenstein et al 1996;Dobie et al 1996;Boyer et al 1997). These observations supported the assumption that integration sites of transgenes are randomly distributed at unreproducible chromosomal sites.…”
Section: Integration Characteristics Of the Pronuclear Injected Transmentioning
confidence: 99%
“…LCRs are short stretches of DNA, characterized by tissue-specific developmentally stable DNase-I hypersensitive sites which are able to provide an open chromatin structure to adjacent sequences even when the transgene is integrated into heterochromatic centromere regions of mouse chromosomes (Festenstein et al 1996). LCRs have been identified, for example, upstream of the globin gene cluster and downstream of the CD2 gene (Orkin, 1990;Lake et al 1990).…”
Section: The Construction Of Transgenesmentioning
confidence: 99%